#### Answer

$(f-g)(x) = 3-x$

#### Work Step by Step

If $f(x) = x$ and $g(x) = 2x-3$
$(f-g)(x) = f(x) - g(x) = x - (2x-3) = x - 2x +3 = -x +3 = 3-x$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(f-g)(x) = 3-x$

If $f(x) = x$ and $g(x) = 2x-3$
$(f-g)(x) = f(x) - g(x) = x - (2x-3) = x - 2x +3 = -x +3 = 3-x$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.